Stuck in the middle is fiscal policy failing the middle class? - Estache, Antonio; Leipziger, Danny M. (Brookings Institution Press, 2009)
"Examines both economic and social public policy initiatives in its assertion that enhancing the welfare of people in developed and developing nations requires an explicit focus on the middle class"--Provided by publisher.